Computational Analysis of Heat Transfer Enhancement in a Circular Tubed Heat Exchanger Using Al\(_2\)O\(_3\) Nanofluids - Ch. Indira Priyadarsini; P. Anjani Devi; V V R Seshagiri Rao (Engineering Research: Perspectives on Recent Advances Vol. 6, 2025)
. Various heat enhancement techniques are available to find the performance of industrial and practical appliances for a more efficient heat transfer rate. One such method is the use of nanofluids, which has emerged as a passive heat transfer technique in numerous applications. Nanofluids are recognized for their significant potential to enhance heat transfer and are particularly well-suited for use in heat transfer processes. In recent years, extensive research has been conducted to better understand the mechanisms behind heat transfer enhancement and control when utilizing nanofluids. The objective of this work is to study the effect of transfer rate in an annular pipe for water and aluminum oxide nanofluid with 0.25% and 0.5 % by volume for Reynolds numbers 2000 and 3000. A numerical method finite volume was used to observe velocity and temperature. Heat transfer coefficient, Nusselt number and overall heat transfer have been calculated from simulation. The design of the annular tube was done in ANSYS workbench; in which the inner tube was assigned with aluminium and outer tube with copper. It is observed that there is an increased rate of heat transfer when nanofluid of Al2O3 with 0.25% compared to 0.5%.